Triband Omnidirectional Circularly Polarized Dielectric Resonator Antenna with Top-Loaded Alford Loop. (1st September 2014) - Cheng, Chunxia; Zhang, Fushun; Yao, Yali; Zhang, Fan
Abstract : A triband omnidirectional circularly polarized dielectric resonator antenna with a top-loaded modified Alford loop for GSM, WLAN, and WiMAX applications is proposed. Fed by an axial probe, the DRA (dielectric resonator antenna) radiates like a vertically polarized electric monopole. The top-loaded modified Alford loop provides an equivalent horizontally polarized magnetic dipole mode at triband. Omnidirectional CP (circular polarized) fields can be obtained when the two orthogonally polarized fields are equal in amplitude with phase quadrature. The antenna has been successfully simulated, fabricated, and measured. The experimental and numerical results exhibit that the antenna can obtain usable CP bandwidths of 1.925–1.955 GHz, 2.36–2.48 GHz, and 3.502–3.53 GHz with return loss larger than 10 dB and axial ratio less than 3 dB. In addition, over the three bands, the antenna obtains very good omnidirectional CP radiation patterns in the azimuth plane. Moreover, an average CP gain in the azimuth plane of 1.2, 1.6, and −1.5 dBic for the lower, middle, and upper bands has been obtained.